Azathioprine versus mycophenolate mofetil for long-term immunosuppression in lupus nephritis: results from the MAINTAIN Nephritis Trial. Issue 12 (10th September 2010) - Houssiau, Frédéric A; D'Cruz, David; Sangle, Shirish; Remy, Philippe; Vasconcelos, Carlos; Petrovic, Radmila; Fiehn, Christoph; de Ramon Garrido, Enrique; Gilboe, Inge-Magrethe; Tektonidou, Maria; Blockmans, Daniel; Ravelingien, Isabelle; et al.
Abstract : Background: Long-term immunosuppressive treatment does not efficiently prevent relapses of lupus nephritis (LN). This investigator-initiated randomised trial tested whether mycophenolate mofetil (MMF) was superior to azathioprine (AZA) as maintenance treatment. Methods: A total of 105 patients with lupus with proliferative LN were included. All received three daily intravenous pulses of 750 mg methylprednisolone, followed by oral glucocorticoids and six fortnightly cyclophosphamide intravenous pulses of 500 mg. Based on randomisation performed at baseline, AZA (target dose: 2 mg/kg/day) or MMF (target dose: 2 g/day) was given at week 12. Analyses were by intent to treat. Time to renal flare was the primary end point. Mean (SD) follow-up of the intent-to-treat population was 48 (14) months. Results: The baseline clinical, biological and pathological characteristics of patients allocated to AZA or MMF did not differ. Renal flares were observed in 13 (25%) AZA-treated and 10 (19%) MMF-treated patients. Time to renal flare, to severe systemic flare, to benign flare and to renal remission did not statistically differ. Over a 3-year period, 24 h proteinuria, serum creatinine, serum albumin, serum C3, haemoglobin and global disease activity scores improved similarly in both groups. Doubling of serum creatinine occurred in four AZA-treated and three MMF-treated patients. Adverse events did not differ between the groups except for haematological cytopenias, which were statistically more frequent in the AZA group (p=0.03) but led only one patient to drop out. Conclusions: Fewer renal flares were observed in patients receiving MMF but the difference did not reach statistical significance.